Combining an internal tension relieving technique with anterior cruciate ligament reconstruction (ACLR) reduces graft failure rate and improves functional outcomes: a systematic review and meta-analysis - Yixin Wen; Wei Huang; Minghui Li; Yong Jiang; Yibo Tong; Hongjun Mei; Junfeng Tan (Journal of Orthopaedic Surgery and Research)
Abstract Purpose Graft rupture is a significant cause of graft failure in anterior cruciate ligament reconstruction (ACLR). To address this issue, clinicians have combined the internal tension relieving technique (ITRT) with ACLR to improve graft stiffness, aiming to reduce the risk of graft failure. The purpose of this study is to compare the graft failure rates and clinical functional outcomes between ITRT-assisted ACLR and conventional ACLR. Methods Following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, a search was conducted in databases including Ovid, PubMed, Web of Science, Embase, Cochrane Library, Wanfang Data, CNKI, and VIP Medical Database for clinical controlled trials comparing the ITRT combined with ACLR to conventional ACLR. The search period spanned from the establishment of the databases to September 2024. Studies meeting the inclusion and exclusion criteria were selected, with two independent reviewers conducting literature screening, quality assessment, and data extraction. Data analysis was performed using RevMan 5.4 software. The evaluated outcomes included graft failure rate, Lysholm Knee Scoring Scale, Tegner activity score, Knee injury and Osteoarthritis Outcome Score (KOOS), International Knee Documentation Committee (IKDC) score, Visual Analog Scale (VAS) score, Single Assessment Numeric Evaluation (SANE), return to sport (RTS) rate, and knee joint laxity. Results A total of 11 studies were included in the final analysis, with 1,339 patients (592 patients with ITRT-assisted ACLR and 747 patients with conventional ACLR). The combined analysis results indicated that, compared to conventional ACLR, ITRT-assisted ACLR showed significant advantages in reducing graft failure rates (RR = 0.44; 95% CI: 0.23, 0.83; P = 0.01), increasing return-to-sport rates (MD = 1.75; 95% CI: 1.05, 2.91; P = 0.03), and improving knee scores (including KOOS score and Tegner activity score) (all P values < 0.05). However, no significant differences were observed between the two approaches in terms of Lysholm knee score, VAS score, IKDC score, and knee joint laxity. Conclusions This meta-analysis highlighted the significance and superiority of combining ITRT with ACLR compared to conventional ACLR, particularly in reducing graft failure rate and improving knee function outcomes. The ITRT-assisted ACLR procedure may represent the optimal approach for minimizing graft failure. However, given the limitations of short-term follow-up and reliance on retrospective studies, more randomized controlled trials and longer follow-up periods are needed to further evaluate the long-term graft failure rates and functional outcomes.